Influence of Motivation on Job Stress, Job Satisfaction and Job Performance at Alam Puri Villa Art Museum and Resort Denpasar - I Ketut Aryanta; Ni Wayan Sitiari; Putu Ngurah Suyatna Yasa (Universitas Warmadewa, 2019)
Employee performance is a very important thing in the company's efforts to achieve its goals. Creating good employee performance is not easy because employee performance can be created if the variables that influence it can be well accommodated and accepted by all employees within an organization or company. In this study employee performance is influenced by job satisfaction, work stress and work motivation. This study aims to explain the effect of work stress on employee performance, the effect of work stress on employee job satisfaction, the effect of motivation on employee job satisfaction, the effect of motivation on employee performance, the effect of job satisfaction on employee performance, how job satisfaction mediates the effect of work stress on employee performance, and how job satisfaction mediates the effect of motivation on employee performance. This research is included in the type of research explaining or explanatory research. This research was conducted at Alam Puri Villa Art Museum and Resort Denpasar. Respondents of this study were 64 employees of Alam Puri Villa Art Museum and Resort Denpasar. Data collection techniques used in research include observation, interview, literature study, questionnaire. Data analysis was performed using PLS (partial least square). The results of this study indicate that work stress has a negative and not significant effect on employee performance, work stress has a negative and not significant effect on job satisfaction, work motivation has a positive and significant effect on proven job satisfaction, work motivation has a positive and not significant effect on employee performance, job satisfaction has a positive and significant influence on employee performance, job satisfaction is not a mediating variable between work stress on employee performance, and job satisfaction mediates the influence between work motivation on employee performance.